Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Structure and gelation mechanism of silk hydrogels - Nagarkar, Shailesh; Nicolai, Taco; Chassenieux, Christophe; Lele, Ashish K. (Physical Chemistry Chemical Physics, 2010)
Silk fibroin was regenerated from cocoons produced by the silkworm Bombyx Mori. Light scattering showed that an aqueous solution of the regenerated silk fibroin (RSF) was made of individual proteins with a weight average molar mass of about 4 x 10(5) g mol(-1) and a hydrodynamic radius of about 10 nm. Gel formation of RSF in acidic solutions was investigated as a function of the pH (2-4), concentration (0.5-10 g L(-1)) and temperature (5-70 degrees C). The structure of the gels was studied using light scattering and confocal laser scanning microscopy. The structure was found to be self-similar from length scales of less than 15 nm up to length scales of about 1 mm, and characterized by a correlation length of a few microns. Gel formation was tracked using turbidity, rheology, light scattering and circular dichroism. Gelation involves the formation of self-similar aggregates with a growth rate that increases exponentially. The protein aggregation is correlated to, and perhaps caused by, the formation of beta-sheets, the fraction of which also increases exponentially with time.

Structure-property relations in regenerated cellulose fibers: comparison of fibers manufactured using viscose and lyocell processes - Sharma, Aakash; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (Cellulose, 2019)
Regenerated cellulose fibers are produced using two industrially dominant technologies: the viscose and lyocell processes. Here, we compare commercially available fibers, prepared using the viscose and lyocell processes. Single fibers are subjected to a variety of mechanical deformations to obtain stress-strain, stress relaxation and stress recovery data. These are fitted to a phenomenological model, whose parameters are interpreted in terms of the fiber semicrystalline microstructure. This simple model does not incorporate the complexities of semicrystalline microstructure. Rather, it represents structure in a semicrystalline polymer fiber in terms of an elastic crystalline phase that coexists with a viscoelastic Voigt-like glassy amorphous phase. Lyocell fibers are characterized by higher values of crystalline modulus relative to viscose. Lyocell fibers also have a higher amorphous phase modulus and a wider relaxation spectrum than viscose, suggesting that amorphous and crystalline phases are dispersed in close connectivity in lyocell. Viscose and lyocell fibers exhibit qualitative similarities in their mechanical response. On stretching, there is a transition in the stress-strain curve from a low strain elastic response at a critical value of strain. This critical strain has been incorrectly attributed to yielding of the fiber. We establish that this critical value corresponds to an apparent yield. When subjected to strains higher than this apparent yield point, the fibers develop a memory of the mechanical deformation. This memory decays slowly, logarithmically with time and is lost over about a day as the fiber structure transitions back to the original as spun fiber. Finally, we demonstrate that on wetting the fibers with water, there is an increase in the apparent yield strain for viscose fibers, but not for lyocell. We interpret these results in terms of the semicrystalline microstructure of the fibers.
Keywords: mechanical properties; Model; Regenerated cellulose; Yielding

Process-induced microstructure in viscose and lyocell regenerated cellulose fibers revealed by SAXS and SEM of acid-etched samples - Sharma, Aakash; Wankhede, Parnashri; Samant, Roopali; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2021)
Regenerated cellulose fibers represent an important class of bioderived commercial fibers. The traditional viscose process requires the use of environmentally harmful carbon disulfide solvent to produce fibers. Lyocell fibers, produced using a more sustainable recent process, exhibit differences in properties from viscose. These differences arise from their semicrystalline microstructure, formed during fiber spinning. It is widely believed that regenerated cellulose fibers predominantly form fringed fibrillar crystals. We optimize acid etching, followed by SEM as an experimental tool to visualize this fibrillar structure. Acid etching provides sufficient topological contrast to directly visualize similar to O(10 nm) fibrils using field-emission scanning electron microscopy (SEM). We combine SEM with small-angle X-ray scattering (SAXS) to reveal other microstructural details. We observe a Bragg peak, indicating the coexistence of stacked lamellar structure with crystalline fibrils for viscose fibers, but not for lyocell. Viscose and lyocell fibers are characterized by partially oriented semicrystalline microstructure. We present a methodology to calculate the Lorentz correction for such microstructure and employ this to analyze the lamellar scattering from viscose fibers using a 1D correlation function approach. We characterize the lamellar microstructure after swelling viscose fibers with water and observe expansion of the Bragg spacing due to water absorption in the amorphous regions. Our data suggest that the water-induced plasticization of amorphous regions is inhomogeneous. Lamellar stacks that are more misoriented from the fiber direction exhibit lower swelling than those along the fiber direction. The experimental methods described in this work reveal interesting details of semicrystalline microstructure in regenerated cellulose fibers, with important implications for the mechanical response of dry and wet fibers. The methods developed here might find use in investigations of other polymer fibers as well.
Keywords: acid etching; crystalline lamellae; fibers; fibrils; Lorentz correction; Regenerated cellulose; SAXS